Mapping the Field of Anti-Colonial Discourse to Understand Issues of Indigenous Knowledges: Decolonizing Praxis - Shahjahan, Riyad Ahmed (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2006)
ABSTRACT. In this paper, I examine some of the past and current issues in anti-colonial discourse by briefly reviewing the ideas of thirteen anti-colonial scholars from different regions of the world. I relate these ideas to the discussion of knowledge production and indigenous knowledges. I also examine some critical areas that require more attention from future decolonizing scholarship and practice. With respect to scholarship, these critical areas include: the question of agency; the ambivalence towards Euro-American thought; recognizing the dynamism among knowledge systems; language accessibility; integrating indigenous ways of knowing, and dismantling the academic regime. In addition, I suggest that the questions of decolonizing one’s spirit and recognizing the importance of spirituality, often ignored, are very important to integrate in decolonizing practice. This paper concludes by challenging anti-colonial scholars to open possibilities for ourselves and others by “walking the talk᾿ in our scholarly endeavours and every day lives. FAIRE UNE CARTE DU CHAMP DU DISCOURS ANTICOLONIAL POUR COMPRENDRE LES THEMES DES CONNAISSANCES AUTOCHTONES : PRAXIS EN DÉCOLONISATION RÉSUMÉ. Dans ce document, j’examine certaines des themes du discours anticolonial passés et présents en passant en revue rapidement les idées de treize penseurs anticoloniaux de différentes régions du monde. Je relie ces idées avec la discussion à propos de la production de connaissance et des connaissances autochtones. J’examine aussi certains espaces critiques qui requièrent plus d’attention pour les études ou des pratiques décolonisatrices. Ces espaces critiques comprennent: la question de l‘agencement, l’ambivalence face aux pensées Euro-americaines, l’identification du dynamisme parmi les systèmes de connaissances, l’accessibilité au langage, comment intégrer les manières autochtones de savoir et comment démonter le régime universitaire. En plus, j’ajouterai que la question concernant la décolonisation de l’esprit et la reconnaissance de l’importance de la spiritualité, souvent ignorées, sont très important pour intégrer des pratiques décolonisatrices. Ce document finit par lancer un défit aux chercheurs anticoloniaux d’ouvrir des possibilités pour nous-mêmes et par les autres, et de « marcher comme ils parlent » (« walk the talk ») dans nos efforts scolaires et notre vie de tous les jours.